Prosecutorial Gatekeeping and Its Effects on Criminal Accountability: The Roman Prosecutor's Office and Corruption Investigations in Italy, 1975–1994. (1st November 2022) - Manzi, Lucia
Abstract: What explains a criminal justice system's persistent failure to prosecute a salient and widespread criminal issue, such as systemic corruption? I argue that this results from the presence of a prosecutorial gatekeeper, namely an institution capable of raising jurisdictional issues strategically for the purpose of appropriating investigations and controlling their outcome. In this article, I examine the effects of prosecutorial gatekeeping on corruption investigations within the Italian context. I analyze the causes and effects of the Roman prosecutor's office use of gatekeeping powers over the years from 1975 to 1994. I show that the Roman prosecutor's office pursued prosecutorial gatekeeping in order to undermine sensitive corruption investigations involving elected officials and state agents. This resulted in the Italian criminal justice system's protracted failure to uncover systemic political corruption. Only a suspension in the use of prosecutorial gatekeeping eventually allowed for the Mani Pulite (Clean Hands) operation to move forward unobstructed in exposing this pervasive criminal system in 1992.